Integration of Webqual Method to Importance Performance Analysis and Kano Model to Analyze System Quality of E-Government: Case Study LAPOR! - Fiena Rindani; Sulistyo Puspitodjati (Jurnal Sistem Informasi, 2020)
The management of public complaints in many institutions in Indonesia has not been managed effectively and integrated. Each institution works partially and not coordinated well. This causes duplication of handling complaint, or worse is a complaint possibly not handled by any of institution, due to the reason that the complaint is not their authority. For this reason, the Government of the Republic of Indonesia established a S4N-LAPOR!. Meanwhile, there are still some deficiencies in LAPOR. This research purpose is to analyze/evaluate LAPOR using an integration of Webqual method to Importance Performance Analysis (IPA) and Kano model. This research is only carried out by analyzing web-based LAPOR services. The questionnaires are distributed to 159 respondents. The webqual method is used to determine the dimension and attributes, while the IPA and Kano model is conducted for data analysis. The integration from the results of both data analysis shows that there are 14-attributes out of 23 that need to be the priority for LAPOR improvements.